The adventures of Super Diaper Baby - Pilkey, Dav, 1966-; Hutchins, Harold (Fictitious character) (London : Scholastic Children's Books, 2002)
Two incorrigible fourth graders named George and Harold create a superhero named Super Diaper Baby and write a comic book about his adventures.
2.5
3-6.
3-6
Keywords: Beard, George -- (Fictitious character); Infants -- Comic books, strips, etc -- Juvenile fiction; Superheroes -- Comic books, strips, etc -- Juvenile fiction; Babies -- Fiction; Cartoons and comics; Humorous stories; Superheroes -- Fiction; Comic books, strips, etc; Graphic novels; Humorous graphic novels; Infants -- Comic books, strips, etc -- Fiction; Superhero graphic novels; Superheroes -- Comic books, strips, etc -- Fiction; Graphic novels; Humorous fiction; Superhero comic books, strips, etc